San Mateo Elderly Ville a Filipino elderly hosing integrated with senior citizen community center, improving indoor environment quality through daylight systems and natural views - Aquino, Roselle Alleli L.; Varona, Maria Faith Y. (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
The San Mateo Elderly Ville : housing for Filipino senior citizens aims to design a housing facility which has a mixed housing types applicable to different economic needs of the senior citizen community ; and is described to be elderly-friendly, walkable environment and has community center which facilitates recreational activities that promotes healthy living. This project will promote safety, livability and comfortable facility that will improve quality of life and well-being of senior citizens in their dignity as human beings and help them to enjoy the fullness of life and also remain living in the community for a short or long period as possible. The research tackles the application of architectural design in solving physical, mental and social issues of Filipino elderly housing in the Philippines. Following the cast study research design, site problems concerning space organization and user needs have been determined through library and information research, agency consultations, space mapping and analysis, user interviews and descriptive statistics.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Housing for elderly; Housing for senior citizens; San Mateo Elderly Ville